Preliminary molecular characterization of foot-and-mouth disease virus SAT-1 topotype III associated with recent cattle outbreaks in Syria - Morshed Kassouha; Yaseen Almohsen; Hazem Altaweel; Abdulkarim Hallak; Abdulkarim Kalballouz (PLoS ONE, 2026)
Foot-and-mouth disease (FMD) is a highly contagious transboundary viral infection that poses a significant threat to the livestock industry globally. In Syria, despite ongoing vaccination programs, recent outbreaks (2025–2026) in cattle and sheep has raised concerns due to insufficient antigenic coverage and rapid transmission. This study aimed to identify and molecularly characterize the FMD virus (FMDV) responsible for the disease in six cattle farms across Hama and Homs governorates in January 2026. Samples from teat vesicular fluid and oral swabs were collected and analyzed using RT-PCR targeting the VP1 region. The six farms tested positive for the SAT-1 serotype, and two positive isolates: Syr-Hama 2026 and Syr-Homs 2026, were sequenced and subjected to phylogenetic analysis using the WRLFMD genotyping tool and MEGA11 software. Molecular analysis identified the causative agent as FMDV serotype SAT-1, marking its first molecularly confirmed detection and molecular characterization of this serotype in Syria. Further genotyping revealed that both isolates belong to Topotype III. The Syrian isolates exhibited high nucleotide identity (98.9%) with each other and significant similarity to sequences recently recorded in Lebanon, Azerbaijan, Iran, and Turkey. Phylogenetic tree confirmed a close relationship with the reference strains such as BOT/1/77. The emergence of SAT-1/III in Syria, alongside the co-circulation of the O/ME-SA/SA-2018 lineage, leads us to hypothesize a complex epidemiological shift likely driven by unregulated animal movement across borders. Although this study has its limitations and is based on a limited sample size, the results underscore an immediate necessity to assess and, if required, revise national vaccination strategies, as well as expanded nationwide surveillance and antigenic characterization are required to determine the diversity of SAT-1 strains circulating in Syria and to inform evidence-based vaccine strain selection.